Portulaca oleracea Polysaccharides Modulate Intestinal Microflora in Aged Rats in vitro - Fu, Qiang; Zhou, Siyi; Yu, Mengting; Lu, Yang; He, Genhe; Huang, Xiaoliu; Huang, Yushan (Frontiers in Microbiology, 2022)
To explore the effect of portulaca oleracea polysaccharides (POP) in regulating intestinal microflora in aged rats in vitro, intestinal microbial composition was analyzed by 16 S rDNA high-throughput sequencing, and the level of short-chain fatty acids in fermentation broth was determined by LC-MS. POP significantly up-regulated the relative abundance of Lactobacillus, Eggerthella, and Paraprevotella and significantly down-regulated Escherichia_Shigella, Bacteroides, and Eubacterium nodatum groups. The pH value and ammonia nitrogen level decreased significantly in the POP-treated group, resulting in more short-chain fatty acid consumption which changed of the acid-base environment of the fermentation broth. In conclusion, POP is beneficial to aged rats because it can regulate intestinal flora, promote the growth of probiotics, and inhibit the reproduction of pathogenic bacteria.